Applied Behavior Analysis (ABA) Methods Strategy and Individual Methods for Autism Child of Development Process in Indonesia - Aulia Nursyamsiah Prasetyo; Purwanti Hadisiwi; Ditha Prasanti (MO.RI Publishing, 2023)
Autism Home Karawang’s branch is the most popular children's special needs school in Karawang society. This school also applies the ABA and individual methods during the learning process because these two methods have been applied to an autistic child and its development has been proven to be faster. This study aims to determine the instructional communication used in the teaching and learning process at Autism Home Karawang, to find out the reasons for using the ABA and individual methods in teaching autistic children at Autism Home Karawang, and to find out what factors support and inhibit the teaching and learning process at Autism Home Karawang. This research provides new findings in the field of educational communication research, particularly regarding learning strategies that can be used by teachers in teaching schools for children with special needs. This research method is qualitative with a case study approach. The data collection techniques are through observation, deep interviews, and documentation. The informant in this study amounted to 6 persons. The result of this study is that the implementation of both methods is quite easy to apply, and makes the child develop quickly. These two methods are applied because they are easy to implement and have been proven to help.